ChatGPT for Language Teaching and Learning - Kohnke, Lucas; Moorhouse, Benjamin Luke; Zou, Di (RELC journal, 2023)
In this technology review, we explore the affordances of the generative AI chatbot ChatGPT for language teaching and learning. In addition to this, we also present debates and drawbacks of ChatGPT. Finally, we present the digital competencies teachers and learners require to use this chatbot ethically and effectively to support language learning.